(Auto) Formação e saberes docentes no desenvolvimento profissional do professor administrador: entre as ciências administrativas e da educação - Coelho Junior, João Carlos (2018)
This thesis is linked to the Group of Studies on Universities (GEU) and to the research line "Training, knowledge and professional development" of the Graduate Program in Education, Federal University of Santa Maria, Rio Grande do Sul, Brazil. This thesis defends to be possible for the administrator teacher to constitute his (self) training and knowledge in the process of professional teacher development and in the dialogue between the specificities of the Administrative Sciences and Education. This idea permeates the main question of the research and its general objective, therefore, the specific objectives were: to map the motivational factors that led the Administration professional to enter and stay in the teaching career; identify which experiences are considered to be significant to constitute the administrator teacher and how they are related to the knowledge of teaching; and recognize how the teacher administrator increases his professional development in the articulation between the specific knowledge of the Administration and the knowledge of teaching. The qualitative research approached a (auto) biographical research for its narrative approach, being the narrative and textual analysis discursive. The context of the research was the Administration Course of a Federal Institution of Higher Education (IFES) in the countryside of Rio Grande do Sul. From a Google Form, sent for all the teachers of the referred course, by e-mail, the profile of the administrator teacher was drawn, being the respondents professionals with Doctorate degree, the majority in Administration, with average age of 46,3 years old. The option for the teaching profession in this context was, predominantly, due to vocational self-discovery for the higher teaching career and the search for professional stability. Half of these teachers say they planned to become a teacher during undergraduation course, and, approximately, 70% took the PhD degree while teaching in IFES. Thus, when they started, they did not have previous preparation for teaching and qualification at the doctorate level. The absolute majority considers the formation and the permanent professional development for the teaching activity to be necessary, and also the participation in events and readings. Regarding professional self-realization, this arises from the contribution to the professional training of many people and the monitoring of personal and professional maturity of students. Traumatic experiences arise from the tensions generated by competitiveness and disrespect among departmental colleagues. It is believed that the knowledge of the administrative and educational sciences are interconnected in the contextualization of the theory, incentive to the permanent reading, organization of the classes and in the management of the projects. Finally, they admit the need for a specific pedagogy, which would be a commitment of the professionals with their area of teaching, authorizing the appropriation of the knowledge of teaching and the pedagogical construction for the development of the course and its protagonists. Moments of memory (re) significance and self-experience have been constituted, valuing individual history and its connection with the history of the institution and the teaching profession itself. In order to do so, ten (10) teachers of the different pedagogical generations of the IFES staff, who agreed to participate in the study, were carefully listened through narrative interviews. The self-narratives were transcribed; the resulting biograms (AN) were forwarded to the participants for review and / or complementation and were interpreted in a narrative analysis phase. Next, the ATD was carried out through the conceptual axes: initial motivational factors and intrinsic to the professional development of the teacher; significant experiences in the constitution of the administrator teacher; permanent formation in university teaching and constructive teaching movements; self-training and self-experience. The conceptual core (central thread) of the narrative set reinforced the importance of the reconnection of knowledge and articulation between specific knowledge of administration and teaching. The narrative corpus was complex and substantial to build the understanding of the (self) formative process of the administrator teacher, as this occurs in his professional development and the interlocution between the knowledge of administrative and educational sciences. Mainly that, being administrator and professor of administration, this presupposes identity and a pedagogy to be configured as the formative base of the teaching profession in higher education. The knowledge of how the teaching is constituted in the specific area of Administrative Sciences broadens the scientific knowledge of the training area and prospects new researches in the field. Likewise, it leads to the development of a network of professional teacher development, in the sense of welcoming the newcomer teachers to advisory actions and producing at the base of teaching a specific pedagogy of the area.